Hubungan Motivasi Dan Hasil Belajar Berdasarkan Keikutsertaan Pada Komunitas Belajar Mandiri Mahasiswa - Dwi Pamungkas; Aung Sumbono (JOURNAL OF SONGKE MATH, 2018)
This study aimed to determine the correlation between motivation and learning outcomes based on participation in self-learning communities on the student of the mathematics department of STKIP Muhammadiyah Sorong, held on 27 April to 27 May 2015, with a population of 132 students and a sample of 30 students.The method used is the experiment that studied quantitatively and qualitatively, of the instrument which tested the reliability and validity. Data written tests and questionnaires are not all normal but all similar samples. Hypothesis test using Paired Sample t-test, Wilcoxon Rank singed, Pearson correlation and Kendall.There is a change on the written test, but there is no correlation between motivation and learning outcomes based on participation in self-learning communities on the student of Mathematics department of STKIP Muhammadiyah Sorong with correlation result test semester IV Sig. (2-tailed) = 0.600 lebih dari 0.05 and semester VI Sig. (2-tailed) = 0,934 lebih dari 0,05.